The Relationship between Neuroticism and Binge Eating Symptoms in Women: The Mediating Role of Body Image Concern and the Moderating Role of Body Appreciation - Mostafa Khanzadeh; Somayeh Abolghasemi; Tayebeh Jafari; Fatemeh Saadatbin Javaheri (مطالعات روانشناختی, 2024)
The purpose of this study was to investigate the mediating role of body image concern in the relationship between neuroticism and binge eating symptoms, considering the moderating role of body appreciation in a non-clinical sample of women. For this purpose, 252 women from Najaf-Abad city (Iran), were selected using convenience sampling method. NEO Five-factor Inventory, Body Image Concern Inventory, Body Appreciation Scale and Binge Eating Disorder Screening Questionnaire were research tools. To test the moderated mediating model, the path analysis method proposed by Hayes was used. The results of the path analysis showed that body image concern plays a mediating role in the relationship between neuroticism and binge eating symptoms in women. Also, the results of the moderating effects of the model showed that body appreciation can moderate the indirect effect of neuroticism and the direct effect of body image concern on women's binge eating symptoms. In general, these findings show that body appreciation can be a protective factor, leading to a reduction of the indirect effect of neuroticism and the direct effect of body image concern on women's binge eating symptoms.